(untitled) (diségno, 2020)
In April of this year, we finally received the notification from ANVUR that the journal diségno has been included in the list of scientific journals recognized in Area 08, starting from the first issue. For our scientific society this is the first of the goals we had set ourselves, to the full benefit of the research and scientific activities of Drawing, indicated as early as in the first editorial by Vito Cardone in 2016 in which he wrote “The project phase of the new journal has been long, and thoroughly meditated. It was developed, after the decision of founding the journal deliberated by UID’s Technical Scientific Committee in November 2016, by a specific work group of the Committee itself, taking into account the numerous suggestions received from various colleagues after the announcement of the important decision” [Cardone 2017, p. 6]. A heartfelt thanks goes to the commitment of its founder, to the work of the Editorial Board coordination committee and to all the staff who have dedicated themselves with such great rigor, adopting all the ANVUR directives with which a “scientific” journal is required to comply. (read more)